The impact of sensory modality on prospective memory: Differences between visual and auditory processing. Issue 5 (May 2023) - Vicentin, Stefano; Cona, Giorgia; Arcara, Giorgio; Bisiacchi, Patrizia
Prospective memory (PM) is the ability to perform an intended action when the appropriate conditions occur. Several features play a role in the successful retrieval of an intention: the activity we are concurrently engaged in, the number of intentions we are maintaining, where our attention is focused (outward vs. to inner states), and how outstanding the trigger of the intention is. Another factor that may play a crucial role is sensory modality: Do auditory and visual stimuli prompt PM processing in the same way? In this study, we explored for the first time the nature of PM for auditory stimuli and the presence of modality-dependent differences in PM processing. To do so, an identical paradigm composed of multiple PM tasks was administered in two versions, one with auditory stimuli and one with visual ones. Each PM task differed for features such as focality, salience, and number of intentions (factors that are known in literature to modulate the monitoring and maintenance requests of PM) to explore the impact of sensory modality on a broad variety of classical PM tasks. In general, PM processing showed similar patterns between modalities, especially for low demanding prospective instructions. Conversely, substantial differences were found when the prospective load was increased and monitoring requests enhanced, as participants were significantly slower and less accurate with acoustic stimuli. These results represent the first evidence that modality-dependent effects arise in PM processing, especially in its interaction with features such as the difficulty of the task and the increased monitoring load.